Determination of the optimum speed for MIG welding of alloy 5086-H116, by hardness test, tensile test and metallographic examination for the manufacture of aluminum tankers - Cabrera Escobar, José Omar; Cabrera Escobar, Raúl Vinicio (Enfoque UTE, 2018)
For the construction of the specimens welded by the GMAW process of the aluminum alloy 5086-H116, advance speeds of 300, 400, 500, 600 and 700 mm / min are used that are within the recommended range, the same as they allowed the energy contributed to the union. From the results obtained in the different tests, it was determined that the most suitable welding advance speed is 500 mm / min (with a contributed energy of 335.34 J / mm), this energy is the most suitable mechanical in the 5086-H116 alloy welding at an amperage of 148 A. At this energy level, the lowest loss of magnesium occurs; the particle size of Al3Mg2 is finer and easier distributed evenly on the α matrix, that allows obtaining the best mechanical properties.